Disintegration of the Muslim ummah and the emergence of the Islamic resurgent movements in the sub-continent: a comparative study of ideologies of the Tablighi Jamaat and Jamaat-i-Islam - Kausar Ali,; Huang Minxing,; Hashmat Ullah Khan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Removing the causes of disintegration and paving the way for the reintegration of the Ummah (global community of Muslims) is one of the main agendas of the revivalist movements. Islamic revivalist movements (henceforth as IRMs) are urging ordinary Muslims to adopt a more conservative outlook in their daily lives. Among these IRMs, the Tablighi Jamaat (TJ) founded by Maulana Muhammad Ilyas and the Jamaat-i-Islami (JI) established by Maulana Maududi have attracted the attention of millions of Muslims. While scholars have extensively studied the origin, ideologies, and Islamization of these Muslim evangelical movements. There is a lack of scholarly literature on the comparative study of both Islamic movements on the question of what factors led to the decay and downfall of the Muslim community. Drawing from various primary and secondary sources, this paper seeks to explore the perspectives of both these revivalist movements on the disintegration of the Muslim Ummah. Both of these Islamic revivalist movements widely believe that Muslims deviated from the true path of Islam, and as a result, God punished them by depriving them of their socio-political glory. The ultimate objective of both the revivalist movements is the same but they have many differences when it comes to implementing their reformation schemes.